Ludwigia litoranea (Onagraceae), a new species from coastal southern Brazil - Pesamosca, Silviane Cocco; Boldrini, Ilsi Iob (Phytotaxa, 2015)
Ludwigia litoranea (Onagraceae) is recognized as a new species from coastal southern Brazil. The new species has close morphological affinities to L. grandiflora and L. hookeri, from which it is distinguished by the narrowly linear stipules and bracteoles with a glandular ovoid apex. Herein are provided the description and illustration together with habitat information and conservation assessment.